Association between before and during early pregnancy hypertension with the gestational diabetes mellitus prevalence: a prospective observational study - Nisa, Zeenat U.; Farooq, Sofia; Khan, Ishtiyaq Ahmad (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Type 2 diabetes mellitus and hypertension are both components of the metabolic syndrome and commonly occur together in individuals. It has been found that blood pressure (BP) predicted the development of incident type 2 diabetes independent of body mass index (BMI) and other known risk factors. Methods: All the women with preeclampsia from 30 weeks onwards were enrolled in the study. The umbilical artery (UA) systolic-diastolic (S/D) ratio >2 standard deviation (SD) or UA-pulsatility index (PI) and UA-resistive index (RI) >2SD were taken as abnormal. The middle cerebral artery (MCA) was visualised and cerebroumblical PI ratio calculated. MCA-RI<2SD was taken as abnormal. Results: The prevalence of GDM in this study was found 13.4 (%). Prevalence of GDM was found to be almost two-fold higher in hypertensive and pre hypertensive patients as compared to normotensive patients (p- 0.009) emphasizing upon the fact that diabetes and hypertension may be connected by the common pathogenic pathways of insulin resistance and endothelial dysfunction. Conclusions: The results of this study are quite indicative of this fact that patients with older age >30 (years) and with history of hypertension and prehypertension should be strictly screened for GDM as GDM was found twice more common in pre-hypertensive and hypertensive group and GDM prevalence markedly increased as the age advanced.